ANALISIS PERPAJAKAN ATAS PREMI ASURANSI : STRATEGI PENGELOLAAN RISIKO DAN IMPLIKASINYA DALAM KONTEKS KEUANGAN - Abdi Mitro Giripati; Fadlan Nur; Abdul Hamid Siregar; Darwin Multa Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Tax imposition on insurance premiums has a significant impact on corporate and individual financial planning. This article analyzes various aspects of taxation of insurance premiums, focuses on risk management strategies, and their implications in a financial context. This study identifies the types of insurance premiums that are subject to tax, explores risk management strategies that can minimize the tax burden, and assesses the impact of taxes on financial decisions.